The Strategy of Jurnal Adabiyah In Publishing Scholarly Papers - Asmiati Abdullah; Gustia Tahir (UPT Perpustakaan UIN Alauddin Makassar, 2020)
One of the scientific publications in academic institutions is a scholarly journal. This study will describe the strategy of Jurnal Adabiyah in UIN Alauddin so that it can still exist until today in publishing scholarly papers and can be recognized as National accredited journal with Grade Sinta 2. The data were obtained through interviews with several journal editors, observations and documentation through the journal website. This research shows that in general outlines there are three strategies undertaken by Jurnal Adabiyah Journal to continue to exist which are maintaining teamwork, holding scientific activities, and promoting the journal. This research can be used as one of references for scientific publications, particularly for scientific journals in UIN Alauddin.ABSTRAKSalah satu media publikasi ilmiah di perguruan tinggi ialah jurnal. Penelitian ini akan menggambarkan bagaimana strategi Jurnal Adabiyah UIN Alauddin Makassar yang hingga saat ini masih eksis menerbitkan artikel-artikel ilmiah dan dapat pengakuan terakreditasi Nasional peringkat Sinta 2. Data penelitian diperoleh melalui wawancara dengan beberapa editor jurnal, observasi dan dokumentasi langsung pada laman website jurnal. Penelitian ini menunjukkan bahwa secara garis besar ada tiga strategi yang dilakukan Jurnal Adabiyah hingga tetap eksis yakni menjaga kerja sama tim, mengadakan kegiatan-kegiatan ilmiah, dan gencar promosi. Penelitian ini dapat dijadikan salah satu rujukan bagi media-media terbitan ilmiah, khususnya jurnal-jurnal ilmiah yang ada di kampus UIN Alauddin Makassar.